Taxonomic Revision of the Asiatic Widespread Filmy Fern Cephalomanes javanicum (Hymenophyllaceae, Polypodiidae) Reveals More Species than Expected - Zhao, Ya-Nan; Regnier, Camille; Boucheron-Dubuisson, Elodie; Iwatsuki, Kunio; Ebihara, Atsushi; Hennequin, Sabine; Dubuisson, Jean-Yves (Plants (Basel), 2025)
This study revises the taxonomy of Cephalomanes javanicum (Hymenophyllaceae), a filmy fern traditionally considered widespread across the Indomalayan and Australasian regions. Through a comprehensive analysis of the literature, type specimens, and herbarium collections, we clarify the taxonomic status of three recognized varieties: typical C. javanicum, C. javanicum var. sumatranum, and C. javanicum var. asplenioides. Morphological, morphometric, and molecular phylogenetic investigations reveal that these varieties represent distinct species rather than intraspecific variants. Additionally, we reassess C. atrovirens, a species often confused with C. javanicum, and confirm that its two previously recognized subspecies also warrant species status. Based on these findings, we propose the elevation of the C. javanicum varieties and C. atrovirens subspecies to full species rank, providing updated taxonomic treatments, synonymy lists, and new lectotypifications. These revisions contribute to a more accurate understanding of species diversity within Cephalomanes and have broader implications for fern taxonomy, biogeography, and conservation in the tropical Asia, Australasian, and Oceanian regions.